Diplomasi Parlemen Indonesia dalam Upaya Deeskalasi Konflik Israel-Palestina Tahun 2023-2024 [The Role of Indonesia’s Parliamentary Diplomacy in Deescalating The Israel-Palestine Conflict: An Analysis of Efforts from 2023-2024] - Rizqullah, Farhan; Aisyah, Aisyah (Sekretariat Jenderal DPR RI, 2025)
The Israel-Palestine conflict has seen a notable escalation following the armed attack by Gaza militias on multiple targets in Israel on October 7, 2023. This event prompted a substantial retaliatory response from Israel, which aimed at both militias and civilian locations in Gaza, further exacerbating an already critical humanitarian crisis in the region. This study aims to analyse the role of the Committee for Inter-Parliamentary Cooperation (BKSAP), the House of Representatives, Republic of Indonesia. (DPR RI) in advocating for Palestinian rights and in efforts to mitigate the escalating conflict from the third quarter of 2023 through 2024. Employing the framework of parliamentary diplomacy, the research investigates the initiatives undertaken by BKSAP in this context. Utilising a descriptive methodology, the research incorporates both primary and secondary data, with a qualitative analysis aimed at providing a comprehensive understanding of the parliamentary diplomatic activities relevant to the Israel-Palestine conflict. The analysis indicate that the parliamentary conducted by BKSAP DPR RI in addressing the de-escalation of the Israel-Palestine conflict proves to be notably effective. The findings reveal that BKSAP’s parliamentary diplomacy functions through bilateral and multilateral channels, adhering to three central principles: Access, Trust, and Flexibility. These principles enhance constructive engagement and underscore the effectiveness of Indonesia’s parliamentary approach in addressing multifaceted geopolitical challenges. Through this dual-channel approach, BKSAP aligns its diplomacy with the human security dimension, highlighting its relevance in resolving conflicts and supporting Palestine’s pursuit of sovereignty.AbstrakKonflik Israel-Palestina mengalami peningkatan eskalasi yang signifikan menyusul serangan bersenjata oleh milisi Gaza terhadap sejumlah sasaran di Israel pada 7 Oktober 2023. Serangan ini memicu respons balasan dari Israel yang menyasar milisi serta wilayah sipil di Gaza, sehingga memperburuk krisis kemanusiaan yang telah berlangsung di kawasan tersebut. Penelitian ini bertujuan untuk menganalisis peran Badan Kerja Sama Antar-Parlemen (BKSAP) DPR RI dalam memperjuangkan hak-hak Palestina dan upaya meredakan eskalasi konflik pada periode kuartal ketiga tahun 2023 hingga 2024. Dengan menggunakan pendekatan diplomasi parlementer, penelitian ini mengeksplorasi inisiatif-inisiatif yang dilaksanakan oleh BKSAP dalam mendukung resolusi konflik. Penelitian ini mengadopsi metode deskriptif dengan memanfaatkan data primer dan sekunder, serta menerapkan analisis kualitatif untuk memberikan pemahaman yang mendalam terkait peran diplomasi parlementer dalam konteks konflik Israel-Palestina. Hasil analisis menunjukkan bahwa diplomasi parlementer yang dilakukan oleh BKSAP DPR RI memiliki efektivitas yang signifikan dalam mendukung upaya de-eskalasi konflik. Diplomasi parlementer BKSAP diimplementasikan melalui jalur bilateral dan multilateral yang berlandaskan tiga prinsip utama: akses, kepercayaan, dan fleksibilitas. Ketiga prinsip ini memungkinkan terwujudnya keterlibatan yang konstruktif dan memperkuat posisi pendekatan parlementer Indonesia dalam mengatasi tantangan geopolitik yang kompleks. Melalui strategi dual-channel, diplomasi parlementer BKSAP secara konsisten diselaraskan dengan dimensi keamanan manusia, sehingga mempertegas kontribusinya dalam mendukung penyelesaian konflik serta memperjuangkan kedaulatan Palestina.